Health literacy in adults with chronic diseases in the context of community health nursing : a scoping review - Annike Morgane Nock; Sabine Metzing; Ivonne-Nadine Jürgensen; Corinna Petersen-Ewert (Nursing reports, 2023)
Health literacy was identified as a main determinant in self-care of chronic diseases. This results in responsibilities for health professionals for daily practice. For primary care setting, special requirements arise due to the heterogeneity of communities. The objective of this scoping review was to explore and map the scope of the research material on strategies led by community health nurses to improve health literacy in (patients with) chronic diseases. This review aimed to identify gaps in the literature and existing approaches on promoting health literacy by community nurse practitioners. The following criteria were included for the research: Adults with chronic diseases, health literacy, community health nursing and primary healthcare. All types of searches for studies from 1970 to present were carried out in electronic databases and in a Google and a Google Scholar search. The search procedure is presented in a flow chart. Results: From all reviewed studies, nine records were included in the review. Findings with regard to the increase in health literacy in self-management of chronically ill patients were identified. Studies focusing on specific demands with regard to the role of community health nurses need to be carried out in depth.
Keywords: health literacy; chronic disease; community health nursing; health literacy strategies; primary healthcare